Corporate social responsibility and the milk market in Poland - Stawicka, Ewa (Turystyka i Rozwój Regionalny, 2018)
Sustainable development was initially associated only with the protection of the natural environment, and eco-development is now an aspect of corporate social responsibility (CSR). Social responsibility refers to responsibility and service to stakeholders interslators, in which three goals should be reconciled: economic, environmental and social. There are more and more good practices, often innovative ones, which have shaped the competitive advantage of Polish companies on the market for some time. The aim of the publication is to analyze and evaluate the development of the concept of social responsibility in milk processing plants in Poland. The basis of the study is the subject literature and a description of practices on the example of TOP companies - the main centers of the dairy industry in Poland. The article is a contribution and a voice in the discussion about showing opportunities and creating a competitive advantage in the aspect of social innovations and changing business models.